Geographical Variation in Wages of Workers in Low-Wage Service Occupations: A U.S. Metropolitan Area Analysis. Issue 2 (May 2019) - Grimes, Donald R.; Prime, Penelope B.; Walker, Mary Beth
Low-wage, service-providing occupations accounted for almost half of all U.S. net job growth between 2006 and 2016. The authors study the variation in wages of low-wage service employees across U.S. metropolitan statistical areas, using cross-sectional estimations for 2016 for the 10th, 50th, and 90th percentile wage rates. New data are used to examine the impact of different cost-of-living adjustments on model results, arguing that the preferred adjustment separates housing costs from other costs. The main results are that strong labor market conditions positively contribute to real wages in most of the categories; minimum wages contribute positively to the 10th percentile of four occupations with evidence of influencing higher wages in the 50th and 90th percentiles; and using the authors' cost-of-living adjustment and controlling for housing costs, the presence of an educated population did not substantially raise wages in the four low-wage, low-skill occupations.